Glycaemic Control Behaviors in Type 2 Diabetes: A Qualitative Study of Patients' Perspectives in Sri Lanka - Amarasekara, A.A.T.D.; Fongkaew, W.; Turale, S.; Wimalasekera, S.W. (University of Sri Jayewardenepura, Nugegoda, 2015)
Introduction: Type 2 diabetes mellitus (T2DM) is escalating globally and now the most important non-communicable disease causing serious health issues in Sri Lanka. The complications of T2DM burden individuals, their families, the economy and the health care system. However, there is limited data on the perspectives of adults about their glycaemic control behaviors in Sri Lanka. Understanding these perspectives is critical in reducing complications, improving health and well-being among adults with T2DM. Objective: To explore the perspectives among adults with T2DM regarding their glycaemic control behaviors. Methods: In this qualitative study, in-depth interviews were conducted among 17 adults with T2DM. Matrix analysis was used to analyze data. Results: Our rich data resulted in two themes centering on reasons for adequate glycaemic control and barriers to glycaemic control. The reasons for good glycaemic control were: understanding the illness, sufficient family support, adequate income, a higher level of education and motivation to control. The barriers were: insufficient knowledge about the illness, low socioeconomic status, lack of family support and poor compliance to health advice. The participants believed that doing diet control, regular exercise and taking medication properly on daily, long-term basis is very challenging. Conclusions: Nurses and health care personnel need to address the barriers and reasons for glycaemic control behaviors in planning, assessment, treatment protocols and health policies to provide better diabetic care in primary health care and hospital settings. It confirms the need for culturally appropriate diabetic care and advice.
Keywords: Glycaemic control; Type 2 diabetes; Diet control; Regular exercise